2000
DOI: 10.1016/s0022-5347(05)67205-9
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit Urinary Bladder Blood Flow Changes During the Initial Stage of Partial Outlet Obstruction

Abstract: Blood flow was approximately 4-fold greater in bladder mucosa than in muscle, which may relate to the significantly higher metabolic rate and lower high energy phosphate concentration of mucosa than muscle. Partial outlet obstruction resulted in a significant increase in blood flow at 1 day post-obstruction, which coincides temporally with the early cellular hyperplasia and hypertrophy of obstructed rabbit bladder. This increase in blood flow may be an essential factor for the initial increase in bladder mass.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 38 publications
1
16
0
1
Order By: Relevance
“…Previous studies (14) demonstrated that PBOO resulted in a significant NOstimulated increase in blood flow at 1 day, which returned to control levels at 3 and 7 days postobstruction. This increase in blood flow would be expected to compensate for the ischemia mediated by the obstruction.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies (14) demonstrated that PBOO resulted in a significant NOstimulated increase in blood flow at 1 day, which returned to control levels at 3 and 7 days postobstruction. This increase in blood flow would be expected to compensate for the ischemia mediated by the obstruction.…”
Section: Discussionmentioning
confidence: 78%
“…In that first study, there were significant differences between muscle and mucosa. We believe this is because the mucosa has a significantly higher blood flow than the muscle, a significantly higher metabolic rate than the muscle and is significantly more sensitive to ischemia/reperfusion; and thus even mild obstruction would lead to oxidative damage to the mucosa, but not the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies used rats (3, 4), mice (1, 10, 11), rabbits (12), guinea pigs (13) and pigs (14) to mimic BOO, whose structural and physiological changes of the bladder wall are similar to those observed in men suffering from BPH (9). …”
Section: Discussionmentioning
confidence: 99%
“…In fact, mice 1 week after obstruction already have a rapid increase in bladder mass, which worsened 3 and 5 weeks after the surgical procedure (11). Similarly, rats and rabbits have increased blood flow after 24 hours of obstruction, which could be the first stimulus for hypertrophy (12, 15). This event occurs due to stretch of the bladder wall components, leading to thickening of epithelium, muscle layer and serosa (16) and increase in synthesis and deposition of collagen (17).…”
Section: Discussionmentioning
confidence: 99%